The Concept of Birrul Walidayn in the Culture and Islamic Education of the Madurese Community - Ismail, Ismail; Muttaqiin, Miftahul; Ridho, Ali; Wardi, Moh.; Supandi, Supandi; Yaacob, Mashitoh; Susanti, R Hariyani (Yayasan Keluarga Guru Mandiri, 2026)
The integration of Madurese culture with Islamic teachings is an important aspect in the study of culture and religion. This study examines birrul walidayn not only from a normative perspective but also by exploring its praxis within the culture and education of the Madurese community. The objective is to understand and explain the concept of birrul walidayn as it is embedded in Madurese culture and education. This study utilizes a qualitative approach, employing data collection methods such as interviews, observations, and document analysis. The data were analyzed through a process that includes reduction, presentation, verification, and the formulation of conclusions. The findings reveal that, according to the Madurese community, birrul walidayn (abhakte ka oreng towa) is a behavior comprising words and/or actions toward one's parents, reflecting devotion, loyalty, obedience, submission, respect, love, and affection, to please the parents. Birrul walidayn refers to a child’s behavior that aligns with values of devotion, loyalty, obedience, submission, respect, and affection, intended to make parents happy with their child's actions. It is not merely about what is spoken or done but is deeply connected to the heart. Actions and speech must align with heartfelt feelings that embody positive values for parents. Birrul walidayn is a social behavioral concept rooted in Islamic teachings derived from the Qur'an and Hadith. The contributions of this study include: enhancing the understanding of contextual Islamic studies, contributing to the fields of anthropology and education, developing social concepts within Islam, and highlighting the relevance of local values in character building.